Unravelling the microscopic characteristics of intrinsically disordered proteins upon liquid–liquid phase separation. Issue 7 (16th December 2022) - Wu, Si; Wen, Jitao; Perrett, Sarah
Abstract: Biomolecular condensate formation via liquid–liquid phase separation (LLPS) has emerged as a ubiquitous mechanism underlying the spatiotemporal organization of biomolecules in the cell. These membraneless condensates form and disperse dynamically in response to environmental stimuli. Growing evidence indicates that the liquid-like condensates not only play functional physiological roles but are also implicated in a wide range of human diseases. As a major component of biomolecular condensates, intrinsically disordered proteins (IDPs) are intimately involved in the LLPS process. During the last decade, great efforts have been made on the macroscopic characterization of the physicochemical properties and biological functions of liquid condensates both in vitro and in the cellular context. However, characterization of the conformations and interactions at the molecular level within phase-separated condensates is still at an early stage. In the present review, we summarize recent biophysical studies investigating the intramolecular conformational changes of IDPs upon LLPS and the intermolecular clustering of proteins undergoing LLPS, with a particular focus on single-molecule fluorescence detection. We also discuss how these microscopic features are linked to the macroscopic phase transitions that are relevant to the physiological and pathological roles of the condensates.